INFORMATION WAR AS THE STRATEGY OF FORMATION OF POLITICAL CONSCIOUSNESS (SOCIAL AND PHILOSOPHICAL ANALYSIS) - Пода, Т. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article analyzes the nature of information wars and its impact on political consciousness and reflection of this impact on social life, shows the dependence of social being and social consciousness from such influences.